Large eddy simulation of unsteady shedding behavior in cavitating flows with time-average validation. (1st October 2016) - Li, Linmin; Li, Baokuan; Hu, Zhiqiang; Lin, Yang; Cheung, Sherman C.P.
Abstract: Cavitation always leads to complex gas–liquid interactions and turbulence structures with multi-scale eddies and vortices. It usually involves cavity growth, break-off and collapse processes; posing great challenges in modeling. This paper focuses on modeling instantaneous cavitating flows using the large eddy simulation (LES) and validating the predictions against experimental data using the time-average method. The volume of fluid (VOF) model was adopted to describe phase equations and coupled with the Schnerr–Sauer cavitation model for describing the evaporation-condensation mass transfer. Simulations were performed to predict the unsteady cavitating flows of both the cylinder and Clark-Y hydrofoil configurations. Firstly, the mechanisms of cavity shedding, vapor cloud forming and collapsing were well revealed. The time-averaged pressure distribution and cavity length around the cylinder were in good agreement with experimental data. Moreover, the periodic cavity shedding and pressure fluctuation around the Clark-Y hydrofoil were also predicted. Different cavity patterns were clearly identified in a typical cycle, and the effect of cavity pattern on hydrodynamic forces was investigated. The computational results of cavity patterns, velocity profiles, drag and lift coefficients were compared with experimental results and good agreements were obtained. The present work provides a valid numerical modeling framework for various cavitating flows. Highlights: The large eddy simulation is used to study unsteady phenomena of cavitating flows. A time-average method is developed to obtain and validate time-averaged fields. The quasi periodic shedding behavior is well revealed. The influence of cavity patterns on pressure distribution is investigated.